A review: The Impact of Environmental Heavy Metal Contamination on Human Health - Hameed Abdulameer, Jihan; Habeeb Obaid, Nada; Jassim Manshad, Maha (Pure Sciences International Journal of Kerbala, 2024)
Heavy metals are a popular threat to the environment because of their toxic effects, tendency to linger in the Earth's atmosphere, as well as capacity to bioaccumulate within the body of an individual. Heavy metal poisoning of ecosystems that are both terrestrial and aquatic is a serious environmental issue that has an impact on human health. The bulk of metallic elements are found in nature, despite the fact that humans produce some of them. Two of the most distinctive features of heavy metals are their atomic mass and the danger they pose to living organisms. Furthermore, despite differences in technology, research on innovative medical diagnostics is still being conducted. The rapidly developing field of nanotechnology is enabling significant advancements in the investigation of mineral material regeneration from complex matrices. Numerous carbon nanomaterials have been employed for the removal of metal, including magnetic nanoparticles, metal oxide nanoparticles, nanotubes, graphene and its derivatives, and nanotubes. Applying nanotechnology to the removal and analysis of heavy metals from food and water sources has many benefits over traditional methods. Among these benefits are high sensitivity, excellent selectivity, minimum limits on detection and measurement, and a wide linear range. Therefore, the goal of the review was to investigate how heavy metals affect the ecosystem, the harm they cause to human health, and the potential for using natural resources to create novel medications. This review also emphasises the application of nanotechnology and non-medical applications to the problem of heavy metal toxicity.